BIMP-EAGA its impact to Mindanao exports - Lunod, Milva L.
This study was conducted in order to evaluate the impact of the Brunei-Indonesia-Malaysia-Philippines East ASEAN Growth Area to Mindanao export to Brunei, Indonesia and Malaysia. In the course of the study, a theoretical framework on export demand was formulated which then served as the basis of the empirical model employed. Furthermore, a combination of qualitative (before and after analysis) and quantitative (using econometric model) method was used in the making and analysis of the study. The main constraint of the study, however, was data unavailabilty. Finally, the impact of EAGA to Mindanao's export industry, from 1991-2001, in terms of export volume, value, trend and growth rate was assessed; the island's exports profile was examined; factorsaffecting its export performance to BIM were identified; policy implications emanating from the study were explored; and recommendations addressed to the concerned policy making body and for further study were then drawn.